An unusual occurrence of multiparasitism by two genera of Strepsiptera (Insecta) in a mango leafhopper Idioscopus clypealis (Lethierry) (Hemiptera: Cicadellidae) in the Philippines - Kathirithamby, Jeyaraney; Mcmahon, Dino P.; Anober-Lantican, Gaudencia M.; Ocampo, Virginia R. (Zootaxa, 2012)
The mango leafhopper Idioscopus clypealis (Lethierry) (Hemiptera: Cicadellidae) from the Philippines is parasitized bytwo genera of Strepsiptera, Halictophagus and Callipharixenos. A redescription of the male Halictophagus fulmeki(Hofeneder), a new record and description of its conspecific female and a key to Halictophagus in the Philippines aregiven, and a new species of female, Callipharixenos philippines sp. n. is described. The inclusion of the family Callipharixenidae as a subfamily Callipharixeninae within the family Halictophagidae is discussed.